Features of sanctions for administrative offences related to driving vehicles - Пархоменко, Павло Іванович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article is sanctified to the issue of the day – theoretical research of features of approvals for thefeasance of administrative crimes for managements by transport vehicles.Author on the basis of analysis ofpractice of application of administrative legislation and order of production in matters about administrativecrimes taking into account the specific of legal relationships in the field of management determines thefeatures of application of approvals transport vehicles in matters about administrative crimes for managementsby transport vehicles.